Print media transformation to digital platform: case study of neraca economic daily mediamorphosis - Haresti Asysy Amrihani,; Irfan Wahyudi,; Yayan Sakti Suryandaru, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This research explains the mediamorphosis process of Neraca Economic Daily which gradually transformed to online media due to the disruption of communication technology by using Roger Fidler’s Mediamorphosis Theory and Media Economic Theory. By the time new communication media comes into existence; the current (or old) forms will not disappear, instead it will keep evolving and adapting. Technological determinism can shape human thoughts and behaviour in a social environment. Therefore, it may direct them to shift from one technological era to another. This research aims to see how the transition of the Neraca Economy Daily, from print media to online media and e-paper due to the disruption of information technology. This research uses descriptive qualitative approaches with interview method. The economic media theory is used to see how the Neraca economic daily sees the opportunity to maintain its media amidst the onslaught of digital disruption. Data used for this research was obtained from interviews, books, articles from national and international journals, media reports and documents which are relevant to this research. This study found that the management of Neraca economic daily keeps trying to produce newspapers everyday despite a small profit margin due to declining circulation. In the meantime, the management of Neraca Economic Daily also publishes an online version (neraca.co.id) and e-paper to maintain the presence of the daily while at the same time trying to find advertisements to maintain the media.